Advanced Necrotizing Enterocolitis Part 2: Recurrence of Necrotizing Enterocolitis - Thyoka, M.; Eaton, S.; Hall, N. J.; Drake, D.; Kiely, E.; Curry, J.; Cross, K.; de Coppi, P.; Pierro, A. (European Journal of Pediatric Surgery, 2012)
Aim of the Study The aim of this study was to report incidence and clinical outcomes of recurrent necrotizing enterocolitis (NEC).Methods Review of infants treated for recurrent episode(s) of NEC at a tertiary Neonatal Surgical Intensive Care Unit over 8 years (January 2002 to February 2011). Demographic, clinical, radiological, and operative data were analyzed and compared using Mann-Whitney or Fisher's exact tests. Data are reported as median (range).Results A total of 212 consecutive infants were referred for surgical evaluation and treatment of NEC (Bell stage II or III). Of these patients, 22 (10%) had suspected recurrent NEC: in 11 of these the primary episode was Bell stage I successfully treated before coming to our institution (suspected recurrent NEC); in the remaining 11, the primary episode was confirmed (Bell stage II or III) NEC successfully treated in our hospital. Birth weight, gestational age at birth, corrected gestational age, weight on admission, gender, need for surgery, stricture, and mortality rates were similar between infants with recurrent NEC and those with a single episode. Long-term parenteral nutrition (PN) dependency (>28 days) was significantly more common following recurrent NEC compared with a single episode. Among the infants with recurrent NEC, medical therapy alone was not successful in the majority (82%) of cases during the first episode and all required surgery during the recurrent episode.Conclusion Infants (10%) referred for surgical treatment of NEC develop recurrence of the disease. Surprisingly, these infants have similar mortality and stricture rates to those with a single episode. However, the incidence of long-term PN dependency was significantly increased in those with recurrent episodes of NEC.
Keywords: necrotizing enterocolitis; recurrence; parenteral nutrition